Đạo hàm của hàm số \(y=\left(x^2-2x\right)\mathrm{e}^x\) là
\(y'=\left(x^2-2x+2\right)\mathrm{e}^x\) | |
\(y'=\left(x^2+2\right)\mathrm{e}^x\) | |
\(y'=\left(x^2-x\right)\mathrm{e}^x\) | |
\(y'=\left(x^2-2\right)\mathrm{e}^x\) |
Chọn phương án D.
Dùng máy tính cầm tay:
Chọn phương án D.
\(\begin{aligned}
y'&=\left(x^2-2x\right)'\mathrm{e}^x+\left(x^2-2x\right)\left(\mathrm{e}^x\right)'\\
&=(2x-2)\mathrm{e}^x+\left(x^2-2x\right)\mathrm{e}^x\\
&=\left(2x-2+x^2-2x\right)\mathrm{e}^x\\
&=\left(x^2-2\right)\mathrm{e}^x.
\end{aligned}\)